2020
DOI: 10.1136/bmj.m2824
|View full text |Cite
|
Sign up to set email alerts
|

Serious violations of health workers’ rights during pandemic

Abstract: States are failing to uphold even basic obligations to essential healthcare workers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…We noticed an association between psycho-verbal (9) and psycho-non-verbal (10). The violence practiced by people with professional relationships (12) occurred in the workplace (15), with emphasis on psycho-verbal violence (9). Aggressors identified as people with some personal connections (11) were responsible for non-verbal psychological (9) violence in public (16) and private ( 14) places, whereas the violence practiced by strangers (13) would occur in public places (16) (Fig 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We noticed an association between psycho-verbal (9) and psycho-non-verbal (10). The violence practiced by people with professional relationships (12) occurred in the workplace (15), with emphasis on psycho-verbal violence (9). Aggressors identified as people with some personal connections (11) were responsible for non-verbal psychological (9) violence in public (16) and private ( 14) places, whereas the violence practiced by strangers (13) would occur in public places (16) (Fig 2).…”
Section: Resultsmentioning
confidence: 99%
“…Healthcare professionals who suffered violence prior to the pandemic (7) reported having suffered psycho-verbal violence (9) during the pandemic, in their workplace (15), although it was demonstrated by weak associations. Their monthly income (4) had little association with aggressors with personal relationships (11) and private locations (14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although those professionals in the frontline are seen as heroes by most people, not everyone acknowledges the importance of the role they play (11). There have been reports of attacks against health professionals not only in Brazil, but worldwide, which includes stopping them from entering public places or using public transportation, discrimination, physical violence and insults (12)(13)(14)(15)(16). Therefore, the strain on the mental health of these professionals may be further exacerbated as a result of violent verbal or physical outbursts from the general public or patients (8).…”
Section: Introductionmentioning
confidence: 99%
“…Several international studies have been carried out during the pandemic addressing discrimination and violence against healthcare personnel (8,13,14), and others on anxiety and mental health (5,6,8,17). However, to date, no studies have been found in Brazil relating anxiety to the violence suffered by healthcare professionals during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%